KERAGAMAN PENGGUNAAN BAHASA PADA MEDIA LUAR RUANG DI KOTA PALU - NFN Nursyamsi; NFN Tamrin (Multilingual, 2019)
The use of Indonesian in outdoor media is increasingly worrying. This can be seen by the increasing number of Indonesian languages being transferred by foreign languages in public spaces. The Indonesians seem to be powerless in their own country and the substance of the Indonesians seems out of frame. By raising the case of the diversity of language use in outdoor media in the city of Palu, this study aims to describe patterns of diversity in language use, especially the use of foreign languages, regional languages, a mixture of Indonesian and foreign languages, as well as the full use of Indonesian in outdoor media in the city of Palu. The method used in this research is the listening method, the method used to obtain data by listening to the use of language that is in outdoor media in the city of Palu. The analysis shows that the pattern of diversity of language use in external media in the city of Palu is dominated by the use of foreign languages. Of the 280 data captured, 41% of outdoor media use foreign languages, mainly English. Furthermore, 34% of outdoor media use a mixture of Indonesian and foreign languages, 23% use Indonesian in full, and only 2% use local languages.keywords: language diversity, outdoor media